Digital Inclusion and Public Service Accessibility in Rural India: Challenges and Policy Responses - Aashutosh Maheshwary; Abhay Pratap Singh (Asian Digital Governance Problems, 2026)
Purpose: This study investigates the influence of digital inclusion on public service accessibility in rural India, with particular emphasis on internet access, device ownership, digital literacy, and frequency of technology use. Subjects and Methods: A quantitative cross-sectional survey was conducted among 412 respondents from rural areas of Uttar Pradesh, Bihar, and Rajasthan using a multistage stratified random sampling technique. Data were collected through structured questionnaires and analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. Results: The findings indicate that digital inclusion and public service accessibility remain at moderate levels. A significant positive relationship was identified between digital inclusion and public service accessibility (r = 0.620, p < 0.01). Regression analysis revealed that all dimensions of digital inclusion significantly influence public service accessibility, with digital literacy emerging as the strongest predictor (β = 0.35). The model explained 50.0% of the variance in public service accessibility (R² = 0.500). Conclusions: Digital inclusion significantly enhances public service accessibility, while digital literacy represents the most critical determinant. Policies integrating infrastructure development with digital skills enhancement are essential for achieving inclusive digital governance in rural India.